2021
DOI: 10.1111/os.12956
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Double Reverse Traction Repositor versus a Traction Table for the Treatment of Intertrochanteric Femur Fractures: A Comparative Study

Abstract: The aim of the present study was to compare the clinical results for unstable femoral intertrochanteric fractures treated with a double reverse traction repositor (DRTR) and those treated using a traction table with the Asia proximal femoral nail antirotation (PFNA-II).Methods: A retrospective study was performed including 95 patients with AO/OTA type 31-A2 and 31-A3 unstable femoral intertrochanteric fractures who underwent DRTR or traction table-facilitated PFNA-II nailing from April 2015 to December 2018 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…This present study investigated the effects of invasive reduction with DRTR combined with PFNA internal fixation in the treatment of unstable femoral intertrochanteric fractures in the elderly and confirmed that the intraoperative reduction time and operation time were significantly shorter in patients who underwent minimally invasive reduction with DRTR compared to those who underwent conventional reduction with TT. However, there were no statistically significant differences in incision length, intraoperative blood loss, fracture healing time, nor Harris score of the hip joint function at one year after the operation, which was consistent with a previous study ( 10 ). The follow-up period of the study was 8–15 months, with a mean follow-up time of 12 months.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This present study investigated the effects of invasive reduction with DRTR combined with PFNA internal fixation in the treatment of unstable femoral intertrochanteric fractures in the elderly and confirmed that the intraoperative reduction time and operation time were significantly shorter in patients who underwent minimally invasive reduction with DRTR compared to those who underwent conventional reduction with TT. However, there were no statistically significant differences in incision length, intraoperative blood loss, fracture healing time, nor Harris score of the hip joint function at one year after the operation, which was consistent with a previous study ( 10 ). The follow-up period of the study was 8–15 months, with a mean follow-up time of 12 months.…”
Section: Discussionsupporting
confidence: 92%
“…There were no other surgery-related complications in any other patient after the operation and during follow-up. Femoral intertrochanteric fractures usually occur in the elderly patients and are associated with poor prognosis and prolonged bed rest, which can consequently lead to high rates of disability and mortality (10). With the increased incidence of intertrochanteric fractures of the femur, there has been a focus on fracture fixation modalities, particularly intramedullary and extramedullary fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But it has some disadvantages,such as having more di culty in reduction, demanding higher technique. By the aid of assisted reduction device [11][12], the surgery is easy to get good reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment has excellent advantages in relieving pain, restoring hip function early, improving quality of life, and avoiding complications such as cardiovascular accidents and lower limb venous thrombosis caused by long-term bed rest. Therefore, there is a clinical consensus on the surgical approach for ITF [3,4,12]. Currently, PFNA has the advantages of easy operation, more minor trauma, and stable fixation compared with other internal fixation, and is characterized by the addition of BO and the essence of minimally invasive surgery while maintaining the firm fixation and biomechanical stability of AO, which is suitable for all types of ITF and is currently one of the primary surgical modalities for clinical treatment of ITF [4,13].…”
Section: Introductionmentioning
confidence: 99%